Zara Hossain is here - Khan, Sabina, 1968- (Scholastic Press, 2021)
"Ever since her family moved to Texas from Pakistan when she was a baby, seventeen-year-old Zara Hossain has only ever called Corpus Christi home. Being the only Muslim girl at her conservative Catholic school, blending in isn't really an option, especially with people like Tyler Benson always tormenting her. But one day Tyler takes thing too far by defacing Zara's locker with a racist message, which gets him suspended. As an act of revenge, Tyler and his friends vandalize the Hossains' house with Islamophobic graffiti, which leads to a violent crime that puts Zara and her family's entire future at risk"--Jacket flap.